2013
DOI: 10.1016/j.ppedcard.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal echocardiography in healthy young adult male baboons (Papio hamadryas anubis): Normal cardiac anatomy and function in subhuman primates compared to humans

Abstract: Implantable, viable tissue engineered cardiovascular constructs are rapidly approaching clinical translation. Species typically utilized as preclinical large animal models are food stock ungulates for which cross species biological and genomic differences with humans are great. Multiple authorities have recommended developing subhuman primate models for testing regenerative surgical strategies to mitigate xenotransplant inflammation. However, there is a lack of specific quantitative cardiac imaging comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…3 ), hinting at continued evolution of these traits across timepoints. These observations mirror common observed morphological differences between humans and other great apes as our skeleton structures, brain size and organization, and heart morphology have all undergone significant changes 49–52 .…”
Section: Discussionsupporting
confidence: 83%
“…3 ), hinting at continued evolution of these traits across timepoints. These observations mirror common observed morphological differences between humans and other great apes as our skeleton structures, brain size and organization, and heart morphology have all undergone significant changes 49–52 .…”
Section: Discussionsupporting
confidence: 83%
“…are typically used as recipients for XTx experiments. 104 Bert et al 141 found high structural and quantitative similarities between the healthy baboon and human hearts in echocardiography studies; specific exceptions are an elevated left ventricular mass in baboons, low pulmonary vascular resistance, thickened walls of pulmonary artery and aorta, an oversized mitral valve orifice and a very large left coronary artery. As baboons are much smaller than humans (20 vs. 75 kg), juvenile swine must be used as organ donors for XTx experiments.…”
Section: Monitoring Of Pig Heart Function After Orthotopic Xtxmentioning
confidence: 99%
“…Measurements were obtained both at sedated baseline and at a maximum cardiac output achieved via dobutamine administration. 19,20 Two-dimensional images for dimensions (Figure E1) and Doppler-derived hemodynamic measurements were captured digitally (X7-2T probe; Philips, Amsterdam, The Netherlands). Pressure gradients were calculated by a modified Bernoulli equation.…”
Section: Cardiac Imaging and Measurementsmentioning
confidence: 99%